Dexmedetomidine potently and reversibly regulates stress-mediated behaviors - Yocca, Frank D.; Dhull, Dinesh K.; Seth, Subhendu; Chugh, Manisha; Sharma, Sameer; Nandabalan, Krishnan; Postma, Friso R.; De Vivo, Michael (Frontiers in Pharmacology, 2025)
AimsDemonstrate that dexmedetomidine is potentially useful for treatment of psychiatric symptoms caused by acute or chronic stress by using relevant rodent models and doses predicted to achieve sufficient brain levels to activate alpha2-adrenoceptors.MethodsIn vitro characterization was performed using labeled GTPγS binding and β-arrestin recruitment. Free brain levels were measured by using microdialysis probes in rats. In vivo behavioral characterization of dexmedetomidine was performed both an acute stress model (forced swim test or despair test) and a repeat stress model with repeat dosing (the open space swim test). Dexmedetomidine was assessed using translational models: the CCK-4 induced panic test in Wistar rats and latency to rapid eye movement sleep (REM sleep). Rotarod assessments (Swiss mice) and a cued memory consolidation model (Wistar rats) were used to ensure that effective doses had no overt effects on motor coordination or memory consolidation.ResultsDexmedetomidine is both more potent (<10 nM EC50) and has higher intrinsic activity than other α2-AR agonists (clonidine, lofexidine or guanfacine). Estimates of free brain levels at efficacious doses are sufficient to activate all 3 α2-ARs. Dexmedetomidine was effective in decreasing immobility (increasing escape behaviors) in the forced swim test after a single acute stress and in the open space swim test after repeat dosing. Effects of dexmedetomidine were completely reversible and no withdrawal effects were observed. Doses used in the open space swim test had no overt effect on the rotarod indicating no impairment of motor coordination. Dexmedetomidine was highly effective in reversing a CCK-4 induced mediated deficit in the elevated plus maze, a translatable model for anxiety and panic. Dexmedetomidine also increased latency to REM sleep and shortened latency to slow wave sleep, positive attributes for a neuropsychiatric drug.ConclusionDexmedetomidine may be a suitable drug for a chronic dosing for a wide range of stress-mediated symptoms, not limited to the acute treatment of agitation. Brain levels are highly predictable based on plasma exposures and are consistent with the known affinity for α2-ARs.